Memórias, discos e outras notas: uma história das práticas musicais na era elétrica (19271971) - Marcos Edson Cardoso Filho (2013)
In 1927, Odeon Recording Company released its first catalog containing electrically recorded discs. The new recording system replaced the metal cone that was used in the mechanical era, with the microphone, which became the main protagonist in the phonography of the new registration period. The electrical recording enabled more effective timbre of instruments and voices, which helped to build new sounds for Brazilian popular music. In this sense, the research presented here aims to map out, within a socio-historical perspective, the musical practices of Brazilian phonography since the arrival of the microphone, a period characterized here as the electrical age of recording. The intention here is not to create a history of recording technologies and studio production in the twentieth century, but to relate the various technological configurations of the electrical age to the changes in socio-musical studio practices and their inevitable influence on the language of recorded popular music. This study combined data from bibliographical sources, iconographic, specialized periodicals, semi-structured interviews with artists and studio technicians, as well as analysis of phonograms of the period with particular attention to the phonography of Mario Reis. This important performer of the electrical age is not given the weight of an object of research here, but he was our guide in the historical narrative throughout the electrical age.Finally, we conclude that the technological mediation and the collaborative studio practices were important tools for the creation of Brazilian popular music as a vehicle for ideas, building consensus and entertainment.